133 The Effects of Chronic Sleep Restriction on Human Oculomotor Behavior. (3rd May 2021) - Evans, Erin; Tyson, Terence; Costedoat, Gregory; Stone, Leland
Abstract: Introduction: Oculomotor behavioral metrics change according to time awake and circadian phase following a distinct pattern of impairment. Acute sleep deprivation (ASD) causes large decreases in pursuit initiation and steady-state gain, and a compensatory increase in saccadic rate without any systematic change in saccadic size. It also causes large deficits in visual processing of direction and speed, and impaired saccade dynamics. Such deterioration likely reflects changes in both higher cortical and brainstem function, explaining in-part how sleep loss and circadian misalignment affect cognition. It is unclear how oculomotor behavior might change according to chronic sleep restriction (CSR). Here, we measured the same eye-movement metrics during CSR. Methods: Twelve healthy participants (6 females) kept a fixed wake-time sleep-wake schedule, at home for four weeks (weeks 1 and 3 = 9h time in bed (TIB); weeks 2 and 4 randomized to 5h or 9h TIB; actigraphy confirmed). Following weeks two and four, participants completed a 13-hour laboratory visit under dim light (<15 lux), where they maintained a semi-recumbent posture and were provided with hourly isocaloric snacks. A visual tracking task was performed hourly to assess pursuit and saccadic responses and visual motion processing. Performance metrics were computed using MATLAB, including pursuit gain (eye speed/target speed), the rate and amplitude of catch-up saccades, and the accuracy and precision of direction and speed processing. Results: As expected, we found a small but significant (t(11)=-2.17, p<0.03) reduction in pursuit gain (mean+/-SEM: -0.028 +/-0.013 with a large (t(11)=2.96, p<0.01) increase in saccadic rate (0.37 +/-0.13 Hz). However, surprisingly, we found a significant (t(11)=-2.52, p<0.03) decrease in the amplitude of catch-up saccades (-0.15 +/-0.06 deg). The only systematic alteration to visual motion processing was a small reduction in horizontal-vertical asymmetry, which was previously observed with ASD. Conclusion: A week of CSR to 5h is associated with only mild impairment in smooth pursuit eye movements with little impact on visual motion processing. However, CSR caused a maladaptive decrease in saccade amplitude that was not observed during ASD. Eye-movement metrics reveal differential neurological effects of CSR versus ASD. Support (if any): Force Health Protection Program, ONR (SAA2402925-1), NASA Human Research Program, and agreement NNX17AE07A